Novel carbon fiber microeletrodes for extracellular electrophysiology - Budai, Dénes; Molnár, Zsolt (Acta Biologica Szegediensis, 2001)
Single- and multibarrel carbon fiber microelectrode blanks were constructed and pulled to electrodes to be used for extracellular recording and microiontophoresis. A unique spark etching method was developed to produce a sharp-pointed, conical carbon tip protruding 15-20 µm from the glass pipette(s). The shape and size of the carbon fiber tip were examined by scanning electron microscopy. In test experiments, extracellular recordings were made from spinal dorsal horn neurons of the spinal cord in anesthetized rats. The sharp carbon tip allowed these electrodes to penetrate the arachnoid membrane over the spinal cord with ease. The electrodes picked up extracellular spikes with an excellent signal-to-noise ratio. Under the given experimental conditions, the peak-to-peak noise level was about 20 µV. To test the performance of the iontophoresis barrels, neurons were stimulated by iontophoretic application of N-methyl-D-aspartate (NMDA) or kainic acid or by noxious heat delivered to the cutaneous receptive fields in the tail. After the iontophoretic ejection of naloxone, the responses to iontophoresed kainic acid and noxious heat were significantly increased. Spikes from dorsal horn neurons were counted and peristimulus time histograms were displayed online by means of a LabView-based system. These carbon fiber microelectrodes are excellent for extracellular spike recording and microiontophoresis and may additionally be suitable for electrochemical measurements and for the development of enzyme- or antibody-based microbiosensors